Financial Innovation and its Impact on Financial Market - Chhetri, Ashmita Dahal; Chhetri, Guna Raj (Journal of Business and Social Sciences, 2024)
The study investigates the relationship between important financial technologies such as ATMs, point-of-sale systems, mobile payments, mobile money, mobile banking, and internet banking, as well as the effects of financial innovations on the financial market. The study, which polled 210 respondents from Nepali financial institutions, discovered that POS systems streamline retail payments while ATMs greatly improve the accuracy, user comfort, and efficiency of the financial market. Although there were problems with transaction speed, app dependability, and user interface design, mobile payment options were still reasonably convenient. Mobile payments enhanced user experience, security, and satisfaction in spite of these obstacles. Although there were still issues with accessibility and trust, mobile money services were seen positively for financial planning and market inclusivity. Although the convenience and dependability of mobile banking were praised, there was room for improvement in the functionality of the app. Although internet banking was commended for its accessibility and transparency, some users had trouble handling their money online. Strong relationships between ATMs, POS systems, mobile payments, and mobile banking and the financial system were discovered by the study, suggesting that these technologies have a beneficial impact on the market.